Analisis Kebutuhan Diklat Guru PAUD dalam Menghadapi Tantangan Pembelajaran di Era Digital - Hosanna Kristina Tobing; Airen Krety; Dina Amanda; Fiki Triwidia Saputri; Folin Angel Purba; Melianna Br. Barus; Nurbetti Sijabat (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to identify the training needs of Early Childhood Education (ECE) teachers in integrating digital-based learning approaches. Despite the availability of digital tools in PAUD Yobel Bersinar Medan, such as projectors and speakers, their effective use in classroom activities remains minimal. A qualitative descriptive method was employed to collect data through interviews, observations, and document analysis. The findings reveal that most teachers face challenges in utilizing digital media, designing technology-integrated lesson plans, and engaging children through interactive platforms. However, the teachers expressed strong motivation and readiness to participate in contextual and practical training. The study highlights the importance of need-based training programs tailored to the actual teaching context. These findings imply the necessity for institutions to develop structured and sustainable professional development programs to enhance teachers' digital literacy and pedagogical skills, ultimately improving learning experiences in the digital era.